Entomopathogenic Fungi and Bacteria in a Veterinary Perspective - Valentina Virginia Ebani; Francesca Mancianti (Biology, 2021)
The present study aimed to review the papers dealing with the biological activity of fungi and bacteria against some mites and ticks of veterinary interest. In particular, the attention was turned to the research regarding acarid species, Dermanyssus gallinae and Psoroptes sp., which are the cause of severe threat in farm animals and, regarding ticks, also pets. Their impact on animal and human health has been stressed, examining the weaknesses and strengths of conventional treatments. Bacillus thuringiensis, Beauveria bassiana and Metarhizium anisopliae are the most widely employed agents. Their activities have been reviewed, considering the feasibility of an in-field application and the effectiveness of the administration alone or combined with conventional and alternative drugs is reported.